The prevalence of physical inactivity amongst brazilian university students: its association with sociodemographic variables (2009)
Objective The prevalence of physical inactivity amongst adults has been increasing worldwide; however, few studies have been conducted on university freshmen. The present investigation was aimed at determining the prevalence of physical inactivity amongst Brazilian university freshmen and its association with sociodemographic variables. Methods The database for the research project entitled, “Evaluating health-related physical fitness of students from the Federal University of Santa Catarina, Brazil,” was used for this study. A total of 762 students (445 males) having 20.2 (4.7) mean age were studied. The participants’ level of physical activity was measured by IPAQ; sociodemographic variables were self-reported and then recorded. The chi-square test and binary logistic regression were used for statistical analysis (significance level was set at p